Adravya Chikitsa- A Ayurvedic Holistic Nonpharmacological Approach to Combat Mental Health- A Short Review - Ashutosh A Debnath; Rajesh S Kolarkar; Aparna N Sathe (International Journal of Ayurveda and Pharma Research, 2022)
In the Ayurveda medical system, diseases are further divided into Shareerika Roga and Manasaroga according to Adhistana. To manage all types of diseases, Chikitsa is divided into three categories namely, Daivavyapashraya, Yuktivyapashraya and Satvavajaya. Daivavyapashraya Chikisa includes measures to combat Daivakrit diseases. Yuktivyapasraya is a form of treatment based on the basic principles of Ayurveda and Satattvavajaya Chikisa can also control mind withdrawing from the unpleasant things. Ayurveda puts extra pressure on Sattvvajaya Chikisha and Daivavyapashraya Chikisa in managing Manovikaras.Among the Trividha chikitsa, Daivavyapashraya Chikisha has been mentioned earlier due to its "Ashukaritva". It works like Vyadhihara because of Devaprabhava. Satwavajaya Chikitsa is a unique non-pharmacological treatment for psychological disorders. Yuktivyapashraya has two types of treatment meaning internal and external. Inside contains Langhan and Brumhan treatments.The treatment is of two types - Dravyabhuta (drug therapy) and Adravyabhuta (non-drug or non-pharmacological therapy). Both species have their significance to varying degrees in different places. The same names of Bheshaja (medicine) such as Pathya, Prayashchitta and Hita also indicate the importance of Adravyabhuta chikitsa. Adravyabhuta chikitsa is recommended for both Sharirika rogas (somatic diseases) and Mansika rogas (psychological disorders). There is a need to thrive Adravyabhuta chikitsa and Dravyabhuta chikitsa to get the results you want and the best conditions for various ailments and to maintain a normal body condition. The various measures of Adravyabhuta chikitsa described in the dispersed manner in Ayurveda are collected, compiled and discussed in this research paper.